2014
DOI: 10.1016/j.drugpo.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial accessibility of drug treatment facilities and the effects on locus of control, drug use, and service use among heroin-injecting Mexican American men

Abstract: Background This study explores the spatial accessibility of outpatient drug treatment facilities and the potential relationship with drug abuse-related outcomes among Mexican American heroin users. Methods Secondary data on 219 current and former heroin-injecting Mexican American men aged 45 and older were drawn from a research study in Houston, Texas. We used geographic information systems (GIS) to derive two spatial accessibility measures: distance from one’s place of residence to the closest drug treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Inconvenient access to medical facilities would also influence adolescents' drug use behaviors to have higher probability to initiate drug use . Therefore, in order to have maximum effectiveness, the locations of medical treatment facilities should meet with the needs of drug users …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inconvenient access to medical facilities would also influence adolescents' drug use behaviors to have higher probability to initiate drug use . Therefore, in order to have maximum effectiveness, the locations of medical treatment facilities should meet with the needs of drug users …”
Section: Discussionmentioning
confidence: 99%
“…It was found that the distance was an obvious impediment to access to health services in regions with fewer populations . However, access to medical or social services was a multidimensional issue between patients and the service delivery system . The locations and distributions of treatment facilities in geography could affect individuals’ willingness to participate in treatment programs and their retention rate .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobin and colleagues explored complex relationships among place, social networks, and substance misuse among African-American men who have sex with men in Baltimore, Maryland (USA). Kao et al (2014) applied geospatial methods to study the relationship of spatial access to outpatient drug treatment facilities to drug use and treatment utilization among Mexican Americans in Houston, Texas (USA) who are current or former heroin users. McNeil and colleagues (2014) expanded research on gender-based violence in drug scenes to include “marginal men” – that is, men who occupy a marginal position in the drug scene because of their income-generation strategies, age, disability, health status, social isolation, or drug use practices.…”
Section: Placing New Populationsmentioning
confidence: 99%
“…For example, Kao et al (2014) explored the spatial accessibility of drug treatment outpatients. In a study by Pang and Lee (2008) to identify the coverage of methadone maintenance clinic to heroin users, GIS was used for the measurement of districtbased geographic coverage in which methadone clinic should be located at the location needed by heroin users.…”
Section: Gis Approach Towards Substance Abusementioning
confidence: 99%